The KP.2-adapted COVID-19 vaccine improves neutralising activity against the XEC variant - Suthar, Mehul S; Manning, Kelly E; Ellis, Madison L; Jain, Shilpi; Bechnak, Kareem; Vander Velden, Jake; Laboune, Farida; Henry, Amy R; Godbole, Sucheta; Kim, Sungjin; Sahoo, Malaya K; Paredes, Isabel; et al. (The Lancet infectious diseases, 2025)
The limitations of this study include the small cohort size, age group, examination of a single timepoint, and unknown effect of previous SARS-CoV-2 exposure or the cellular immune responses. The funders played no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication. MSS served in an advisory role and received funds to conduct research from Ocugen.